Reviews (New blackfriars, 1967)
VATICAN OBSERVED, by John Moorman, Bishop of Ripon. VATICAN POLITICS: AT THE SECOND VATICAN COUNCIL. 1962–5. by George Bull (Chatham House Essays. JESUS AND THE ZEALOTS, by S. G. F. Brandon. THE THEOLOGICAL TENDENCY OF CODEX BEZAE CANTABRIGIENSIS IN ACTS, by Eldon Jay Epp. (Society for New Testament Studies Monograph Series. 3.) THREE FOURTEENTH-CENTURY ENGLISH MYSTICS, by Phyllis Hodgson. WHAT IS MYSTICISM?, by David Knowles. JOHN HENRY NEWMAN, by C. S. Dessain. Nelson. LETTERS FROM A TRAVELLER, by Pierre Teilhard de Chardin COMMONWEAL. Vol. LXXXV. No. 18, 10th February. 1967. Special issue on GOD. THE GOD I WANT. Edited and introduced by James Mitchell. THE LIVING ROCKS: INTRODUCTION TO BIOPHILOSOPHY FOR TECHNOLOGICALAGE MAN, by A. Harry Walters.